Performance and path coefficient analysis of soybeans under-local conditions - Yap, T. C.; Lee, L. F. (Faculty of Agriculture, University of Malaya, 1975)
Twenty-five varieties of soybean were evaluated in the Faculty farm. The results indicated that some varieties performed quite well under local conditions. Ten of them yielded more than 2,000 kg/ha which is above the average for most soybean-producing countries. The protein content of these varieties ranged from 41.6 to 48.7%. Substantial amounts of variation were found for all agronomic characters observed. Plant height, number of nodes and seeds per plant contributed relatively greater direct effects upon the correlations found with yield in the path coefficient analysis. These findings revealed that these three characters were the main determinants of seed yield in the varieties evaluated here.